Islamic domestic courtyards - Spahic, Omer (International Islamic Publishing House (IIPH), 2020)
This book discusses the uniqueness of courtyard in Islamic domestic architecture. It focuses on its origins and diverse functions, and maintains that it has cultural, environmental, structural and above all, religious connotations as the message of Islam presided, by and large, over the inception and proliferation of what later became known as the Islamic domestic courtyard. Indeed, there were many other contributing factors, however, Islam’s hierarchy of standards and morals was the most important force that furnished the domestic courtyard both in essence and identity, rendering the many indigenous geographical, climatic, cultural and other inherited factors and features rather ancillary, albeit without intending to diminish or downplay the latter’s position and importance. The book is divided into seven chapters. Since the domestic courtyard is fundamental to the remarkable societal stature of the house, it was but appropriate to start the book with a chapter containing some general information on the relationship between spirituality and the house in Islam. The next two chapters discuss the uniqueness of domestic courtyard in general, and the Islamic domestic courtyard, in particular. The following four chapters deal with the functions of Islamic domestic courtyard and how they are affected by climate, environment, privacy and recreation factors while operating within the Islamic ideological framework and system.